Ultra-sensitive FISH is a useful tool for studying chronic HIV-1 infection - Deichmann, Martin; Bentz, Martin; Haas, Rainer (Journal of virological methods, 1997)
Using an ultra-sensitive fluorescence in situ hybridization (FISH) protocol, integration sites of the human immunodeficiency virus-1 (HIV-1) were mapped in two model cell lines for chronic HIV infection. In the promonocytic cell line U1/HIV-1, the two integrated copies of proviral HIV-DNA were located on the short arm of one copy of chromosome X (band Xp21) and on a rearranged chromosome 6. In the T-cell line 8E5/LAV, the single copy of proviral HIV-DNA was integrated into chromosomal bands 13q14-q21, which are known to contain common fragile sites. In addition, ultra-sensitive FISH was used for the detection of HIV provirus sequences in interphase cells, achieving a high hybridization efficiency. This application allows the analysis of the HIV status on a single cell level and thus may become a useful tool for the study of HIV infection.